Neo-liberalism, the rise of the unelected and policymaking in Thailand : the case of the medical tourism industry - Pitakdumrongkit, Kaewkamol (2021)
This article discusses how neo-liberal ideas about development take root when they encounter the very different political and economic context of a developing economy. It analyses Thailand’s medical tourism industry, earmarked by Thailand’s government as one of several priority industries to boost the economy in the aftermath of the 1997 Asian Economic Crisis, which ravaged Thailand and ushered in a group of unelected actors–“reign-seekers”–intent on disbursing supposedly de-politicised neo-liberal governance reform. This article makes three inter-related arguments. First, these unconventional actors function as a fluid intermediary linking various public agencies, private sector players and civil society actors, fostering dialogue and reconciling diverging interests. Second, the influence of neo-liberalism on the workings of the state has been relatively modest as the “reign-seekers” have primarily promoted welfare-oriented policies over pro-business ones. Third, the “reign-seeking” elites’ welfare-oriented stance underlines the fracture and heterogeneity within a group of supposedly neo-liberal proponents.